2011
DOI: 10.1093/cid/ciq248
|View full text |Cite
|
Sign up to set email alerts
|

Update on Human Immunodeficiency Virus (HIV)-2 Infection

Abstract: Infection with human immunodeficiency virus type 2 (HIV-2) occurs mainly in West Africa, but an increasing number of cases have been recognized in Europe, India, and the United States. In this era of global integration, clinicians must be aware of when to consider the diagnosis of HIV-2 infection and how to test for this virus. Although there is debate regarding when therapy should be initiated and which regimen should be chosen, recent trials have provided important information on treatment options for HIV-2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
154
1
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 202 publications
(162 citation statements)
references
References 62 publications
1
154
1
6
Order By: Relevance
“…Observance of nondetected result from the second VBD analyzed for viral load might imply that the HIV-1 was below detectable level of the real-time PCR. Again, it might mean that this particular VBD was positive for HIV-2 which is less virulent and have lower progression to AIDS compared to HIV-1 [12]. Studies have showed the inverse relationships between HIV viral loads and CD4+ T-lymphocytes [45,46].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Observance of nondetected result from the second VBD analyzed for viral load might imply that the HIV-1 was below detectable level of the real-time PCR. Again, it might mean that this particular VBD was positive for HIV-2 which is less virulent and have lower progression to AIDS compared to HIV-1 [12]. Studies have showed the inverse relationships between HIV viral loads and CD4+ T-lymphocytes [45,46].…”
Section: Discussionmentioning
confidence: 95%
“…Despite this advocacy, majority of blood donors in resource-limited settings are replacement blood donors and paid blood donors which are associated with higher risks of transmitting bloodborne infections including HIV. Several studies have documented the prevalence of HIV infections in prospective blood donors in various regions of the world [8,[12][13][14][15][16][17]. Transfusion of blood and blood products has been reported to account for 5-10% of HIV transmission in sub-Saharan Africa [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Human immunodeficiency virus type 1 (HIV-1) infection is a major cause of the AIDS pandemic while HIV type 2 (HIV-2) is the leading cause of disease in some regions of the world [1,2]. This is important when considering the diagnosis of HIV-2 infection, which has different important features compared to HIV-1.…”
mentioning
confidence: 99%
“…HIV-2 was first described in West Africa but after a while spread to other regions of Africa, Europe, India, and America [1]. The increase of migration from countries where HIV-2 is endemic to industrialized countries has facilitated the spread of the virus.…”
mentioning
confidence: 99%
See 1 more Smart Citation